ELECTRONIC WASTE FORECASTING SYSTEM (EWAFS): A TOOL FOR PROPER E-WASTE SEGREGATION AND ADEQUATE HANDLING - Sarucam, Jae-an V; Bajao, Naomi A; Patindol, John Lemnil C; Castro, Rianne R; Matedios, Bonibeth O (Journal of Agriculture and Technology Management, 2023)
Cebu Technological University (CTU), with more than ten external and satellite campuses, has taken its outstanding share in alleviating the threats posed by mishandling solid wastes, including e-waste. Across the province of Cebu, the CTU administration has stretched out the responsible solid waste segregation and disposal campaign. It has taken steps toward helping the community become aware of sound solid waste management. However, no measures have been taken to properly handle unusable compact discs (i.e., CDs, DVDs), chargers, and other electrical and electronic wastes. Hence, there is a need to start seriously considering the proper forecasting and handling of these potentially harmful wastes by gathering enough evidence to support establishing an E-waste Management Center. This study aimed to design and test a system that will store Electrical and Electronic Equipment information in a database upon acquisition for proper tracking and e-waste volume forecasting. It provided an estimate for Recycling, Reusing, and Reducing opportunities. In developing the software, the researchers used the Agile Model, which consists of the following phases such as planning, analysis, design, implementation, testing, deployment, tracking, and monitoring. The software application features included Supply Office Inventory, Maintenance Inventory, E-waste Inventory, Adding New Item to Inventory, Update Information, and Update Status from Inventory, Update Status from Maintenance, Update Status from E-waste, and Report Generation Module. Updating the status for Inventory and Maintenance means tagging the equipment as working, for repair, or salvage. Updating the equipment status from e-waste means tagging it for recycling, reuse, or salvage. The software application testing was done and resulted in the successful implementation of the needed features and functionalities.